2011
DOI: 10.3233/jad-2011-101704
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Heterogeneity of the GRN Asp22fs Mutation in a Large Italian Kindred

Abstract: The Asp22fs(g.63_64insC) mutation in progranulin gene (GRN) has been so far reported in one patient who developed frontotemporal dementia (FTD) at the age of 65. Here, we describe the clinical heterogeneity associated with the GRN Asp22fs mutation in a large Italian family. Clinical and instrumental workup of two symptomatic carriers in two generations has been carried out, together with genetic analysis of probands and of nine asymptomatic family members. The first proband was a 47-year old male clinically di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 20 publications
3
25
0
1
Order By: Relevance
“…White matter changes such as gliosis and demyelination have long been observed in histological studies of FTD (Englund & Brun, 1987) and several groups have observed significant WMH on MRI brain scans of GRN mutation carriers with FTD who lack vascular risk factors (Caroppo et al, 2014; Ameur et al, 2016; Kelley et al, 2009; Le Ber et al, 2008; Paternicò et al, 2016; Pietroboni et al, 2011; Sudre et al, 2017). However, studies that have characterized in detail the pathological correlates of WMH in GRN mutation associated FTD have until now been lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…White matter changes such as gliosis and demyelination have long been observed in histological studies of FTD (Englund & Brun, 1987) and several groups have observed significant WMH on MRI brain scans of GRN mutation carriers with FTD who lack vascular risk factors (Caroppo et al, 2014; Ameur et al, 2016; Kelley et al, 2009; Le Ber et al, 2008; Paternicò et al, 2016; Pietroboni et al, 2011; Sudre et al, 2017). However, studies that have characterized in detail the pathological correlates of WMH in GRN mutation associated FTD have until now been lacking.…”
Section: Discussionmentioning
confidence: 99%
“…However, WMH are less commonly seen in frontotemporal dementia (FTD). Several studies have now reported prominent WMH in patients with familial FTD due to progranulin ( GRN ) mutations (Caroppo et al, 2014; Ameur et al, 2016; Kelley et al, 2009; Le Ber et al, 2008; Paternicò et al, 2016; Pietroboni et al, 2011; Sudre et al, 2017) but the pathological changes underlying these have not previously been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Some individuals with familial FTD caused by GRN mutations had a biomarker profile typical of AD, with decreased Aβ 42 and increased p-tau and t-tau CSF levels [36,37]. However, in other cases, p-tau and t-tau levels were within normal range [38,39]. C9ORF72 repeat expansion carriers were found to have either CSF profiles within a normal range or profiles similar to those of AD patients, with decreased Aβ 42 and increased p-tau and t-tau levels [39,40,41,42,43].…”
Section: Resultsmentioning
confidence: 99%
“…The serum PGRN levels of the 6 AD patients with an atypical CSF biomarker profile were similar to the ones in the typical-AD CSF profile group. So far, only a few patients clinically diagnosed with MCI or AD have been identified with PGRN mutations [38,39,40,41]. …”
Section: Discussionmentioning
confidence: 99%
“…In FTLD populations, PGRN mutation frequency ranged from 5 to 26% (http://www.molgen.ua.ac.be/FTDmutations and Cruts et al [35]) and the spectrum of clinical presentation of the mutation carriers is considerably heterogeneous, even in family members carrying the same mutation [36,37]. Besides the classical FTLD presentations, PGRN mutation carriers have been associated with other clinical diagnosis such as mild cognitive impairment (MCI) [38], AD [39,40,41], Parkinson's disease [40], CBS [41,42,43] and progressive supranuclear palsy (PSP) [44,45]. All pathogenic mutations identified so far are loss of function mutations, most of them leading to premature termination codons, and are predicted to be degraded by nonsense-mediated mRNA decay, producing null alleles [15,16,46].…”
Section: Introductionmentioning
confidence: 99%